Pastoral care in medieval England
1 online resource
Keywords: Pastoral Care, the religious mission of the Church to minister to the laity and care for their spiritual welfare, has been a subject of growing interest in medieval studies. This volume breaks new ground with its broad chronological scope (from the early eleventh to the late fifteenth centuries), and its interdisciplinary breadth. New and established scholars from a range of disciplines, including history, literary studies, art history and musicology, bring their specialist perspectives to bear on textual and visual source materials. The varied contributions include discussions of politics, ecclesiology, book history, theology and patronage, forming a series of conversations that reveal both continuities and divergences across time and media, and exemplify the enriching effects of interdisciplinary work upon our understanding of this important topic.